A new method for identifying fractures in tight sandstone of a gentle structural area using well logs. Issue 11 (26th July 2020) - Guo, Qing; Wang, Xuanyi; Qu, Le
Abstract: In this paper, we conducted a systematic study on the development characteristics and logging prediction of fractures of the Upper Paleozoic tight gas sandstone reservoirs in the eastern Ordos Basin. A new fracture prediction method was proposed based on the variable scale fracture probabilistic model. The calculation steps of this method were as follows: First, the sensitivity of each conventional log series to the tight sandstone fractures was analyzed. It was found that acoustic time difference (AC), density (DEN), natural gamma ray (GR), and deep investigate double lateral resistivity (RD) have good log responses to fractures. Then, the ratio of the range ( R ) to the standard deviation ( S ) of the log data was obtained. Finally, the second derivatives of the log series AC, DEN, GR, and RD were calculated, and a new fracture index was constructed (integrated second derivative, F C ) using the multiple regression method. The fracture recognition rates of this method are distributed in 64.3%‐85.7%. Therefore, the constructed integrated second derivative ( F C ) based on conventional logs is effective to quantitatively characterize the fracture development of tight sandstone. Abstract : Taking the Upper Paleozoic tight sandstone gas reservoirs in the gentle tectonic zone of the eastern Ordos Basin as an example, we proposed a new method for identifying tight sandstone fractures in a gentle structural area using conventional logging data. This study has reference value for the prediction of tight sandstone reservoir sweet spots in gentle tectonic areas worldwide.